Gas-forming abscess associated with prosthetic vascular graft infection caused by Bacteroides fragilis - Motoshi Iwao; Takehiro Hashimoto; Ryota Tanaka; Kazufumi Hiramatsu; Hiroki Itoh (Brazilian Journal of Infectious Diseases)
Introduction: Prosthetic Vascular Graft Infection (PVGI) is a rare but serious complication of open surgical repair of abdominal aortic aneurysm. We report a case of gas-forming abscesses associated with PVGI caused by Bacteroides fragilis identified from the drainage fluid and blood cultures. Case presentation: A 67-year-old man with a complaint of worsening low back pain underwent an emergency open surgery due to abdominal aortic aneurysm. On postoperative day 18, an abdominal CT showed gas formation within the aneurysm. Gram staining of the drainage fluid revealed Gram-negative rods and 16S rRNA gene sequencing performed on the fluid identified B. fragilis, although the culture of the fluid was negative. PVGI caused by anaerobic bacteria such as Bacteroides spp. is relatively rare. The sensitivity of 16S rRNA gene sequencing for culture-negative specimens is generally low, but 16S rRNA sequencing-positive rate increases when a Gram stain of specimen is positive.